Identification of Flow Behaviour for Drainage Elevation Profiling - Mohammad Hardi, Mohammad Aiman; Anjang Ahmad, Mustaffa (Recent Trends in Civil Engineering and Built Environment, 2021)
Floods are a natural disaster that often occurs every year in this country. Floods occur due to the several factors but the main factor of the floods is due to the failure of the drainage system to accommodate the excessive flow of water that causing flash floods. This study is to study the effectiveness of drainage system in Bukit Bakri, Muar, Johor. This area is an area that is often flooded when continuous heavy rains. The objective of the study was to identify drainage inventory along study case and to analyze a drainage elevation profiling. This study can help increase the effectiveness of the drainage system in the area and can reduce the risk of flash floods. As is well known, floods can cause huge losses to flood victims such as loss or damage of property and worse when can cause loss of life. Using the survey data that be collected at the site area it be helped in proposed a new drainage that more effective. The value of discharge that be calculated can determine the effectiveness of the drainage system. The highest value of discharge flows the more effectiveness the drainage system. The time of storm duration must be exceeded of time concentration that is more than 37 minutes. With this study it can help to avoid the flood at the study area and also can reduce the loss to flood victims.